A cross-sectional study of risk factors associated with hypertension in heart and kidney disease patients in Sana'a, Yemen - Muafa, Hussein Mussa; Balkam, Malika Abdu (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertension is a major contributor to cardiovascular and renal disease worldwide, particularly in low-resource settings such as Yemen.ObjectiveTo identify demographic, clinical, and lifestyle-related factors associated with hypertension among heart disease (HD) and kidney disease (KD) patients in Sana'a.MethodsA cross-sectional study was conducted on 300 patients (200 men, 100 women; aged 35–70 years) between March and August 2024. Data on age, sex, weight, smoking, Qat chewing, diabetes, and antihypertensive medication adherence were collected. Blood pressure was measured using a standardized sphygmomanometer. Logistic regression was used to calculate odds ratios (ORs) and 95% confidence intervals (CIs).ResultsHypertension was significantly associated with age (OR: 1.08; 95% CI: 1.02–1.11), obesity (OR: 2.42; 95% CI: 1.23–4.75), smoking (OR: 1.88; 95% CI: 1.05–3.35), type 2 diabetes (OR: 2.87; 95% CI: 1.56–4.55), and irregular medication use (OR: 3.21; 95% CI: 1.45–7.11). All participants reported Qat chewing (100%).ConclusionAge, obesity, smoking, diabetes, and poor medication adherence are major predictors of hypertension in Yemeni HD and KD patients. The universal irregularity in medication use highlights systemic healthcare gaps. Strategies to improve adherence, promote lifestyle modification, and strengthen healthcare systems are urgently needed.